86 Skeletal response to whole body vibration and dietary calcium and phosphorus in growing pigs. (29th July 2019) - Huseman, Chelsie; Welsh, Thomas H; Sigler, Dennis; Suva, Larry; Dominguez, Brandon; Paulk, Chad B; Vogelsang, Martha
Abstract: Whole body vibration (WBV) is reported to elicit increased bone mass and strength. This experiment was designed to determine the effects of whole body vibration (WBV) and dietary calcium (Ca) and phosphorus (P) on bone microarchitecture and turnover. A total of 26 growing pigs were utilized in a 60-d experiment. Pigs were randomly assigned within group to a 2 × 2 factorial with Ca and P concentration (low and adequate) and WBV. Low Ca, P diets were 0.9 g/kg less than recommended levels of Ca and available P. Pigs receiving WBV were vibrated 30 min/d, 3 d/wk at a magnitude of 1-2mm and frequency of 50 Hz. On d 0, 30, and 60, digital radiographs were taken to determine bone mineral content by radiographic bone aluminum equivalency (RBAE) and blood was collected for bone formation biomarker (osteocalcin, OC) and bone resorption biomarker (carboxy-terminal collagen crosslinks, CTX-I). At d 60, pigs were harvested and the left third metacarpal bone was excised for analysis by micro computed tomography (microCT) to measure trabecular microarchitecture and cortical bone geometry. Maximum RBAE values for the medial or lateral cortices were not affected (P > 0.05) by WBV. Pigs fed adequate Ca and P tended (P = 0.10) to have increased RBAE max values for the medial and lateral cortices. Vibrated pigs had decreased CTX-1 concentrations (P = 0.044). Pigs fed decreased Ca and P had increased (P < 0.05) concentrations of OC. Vibrated pigs had lower trabecular number (P = 0.002) and increased trabecular separation (P = 0.003), whereas cortical bone parameters were not changed by WBV or diet (P > 0.05). Whole body vibration in this study did not elicit an osteogenic response; however, early indications of bone turnover were observed.